Lithium disilicate microcrystal dental porcelain powder and preparation method thereof

By using a combination of lithium disilicate glass ceramic powder and basic glass powder, the problem of falling off after molding of dental porcelain powder is solved, the thermal expansion coefficient matching with the bottom crown material and the bonding strength are improved, and the stability of dental porcelain is improved and Overall performance.

CN119306399AActive Publication Date: 2025-01-14LINGJIU INNOVATION (SICHUAN) BIOTECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411400451.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-14
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

Existing dental porcelain powder is prone to collapse and fall off after forming, and cannot match the thermal expansion coefficient of the bottom crown material, resulting in poor stability of the restoration.

Method used

The lithium disilicate microcrystalline dental porcelain powder formed by combining lithium disilicate glass ceramic powder and basic glass powder has a thermal expansion coefficient that matches the bottom crown material, has a high-strength rod-shaped crystal interlocking structure and improved bonding strength The characteristics of the ceramic layer prevent cracking and falling off.

Benefits of technology

The thermal expansion coefficient is achieved with the bottom crown material, which enhances the stability and bonding strength of the porcelain layer, prevents falling off, and improves the overall performance of dental porcelain.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306399A_ABST
    Figure CN119306399A_ABST
Patent Text Reader

Abstract

The invention provides lithium disilicate dental porcelain powder and a preparation method thereof, and belongs to the technical field of dental restoration. The lithium disilicate microcrystal dental porcelain powder comprises lithium disilicate glass ceramic powder and basic glass powder, wherein the lithium disilicate glass ceramic powder is prepared from the following chemical components: SiO2, Li2O, Al2O3, K2O, P2O5, F and TiO2; the lithium disilicate glass ceramic powder is prepared from the following chemical components: SiO2, Li2O, Al2O3, K2O, NaO2, F, SnO2, CaO and MgO. The thermal expansion coefficients of the lithium disilicate glass ceramic powder, the basic glass powder and the lithium disilicate microcrystal dental ceramic powder formed by the lithium disilicate glass ceramic powder and the basic glass powder are well matched with the thermal expansion coefficient of a bottom crown material. Meanwhile, the lithium disilicate glass ceramic powder is high in strength, and a rod-like crystal interlocking structure formed by the lithium disilicate glass ceramic powder can effectively prevent the ceramic layer from cracking; the basic glass powder can improve the bonding strength with the bottom crown and prevent the ceramic layer from falling off.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dental restoration, and in particular to a lithium disilicate microcrystalline dental porcelain powder and a preparation method thereof. Background Art

[0002] During the processing of all-ceramic dentures, the bottom crown is generally made of zirconium oxide, lithium disilicate glass ceramics, aluminum hydroxide and other materials. Then, dentin porcelain, enamel porcelain or incisal transparent porcelain is built up on the surface of the bottom crown, and finally it is glazed externally to finally make a restoration comparable to natural teeth.

[0003] At present, there are two main types of dental porcelain powders on the market for building dentin porcelain, enamel porcelain or transparent porcelain on the surface of the bottom crown. One is German VITA porcelain powder, the main crystal phase of which is leucite; the other is Swiss Liechtenstein Yijia porcelain powder, the main crystal phase of which is fluorine mica. However, the above dental porcelain powders have the phenomenon of porcelain collapse after molding and are easy to fall off from the bottom crown during use. Summary of the invention

[0004] The present invention is to overcome the problem of easy falling off of existing dental porcelain powders, and provide a lithium disilicate dental porcelain powder and a preparation method thereof. The thermal expansion coefficients of lithium disilicate glass ceramic powder, basic glass powder and lithium disilicate microcrystalline dental porcelain powder formed by the above two are all 10-11*10 -1 K -1 , which is very compatible with the thermal expansion coefficient of the bottom crown material. At the same time, lithium disilicate glass ceramic powder has high strength, and the rod-shaped crystal interlocking structure it forms can effectively prevent the porcelain layer from cracking; the base glass powder can improve the bonding strength with the bottom crown and prevent the porcelain layer from falling off.

[0005] The technical solution adopted by the present invention is:

[0006] A lithium disilicate microcrystalline dental porcelain powder, comprising lithium disilicate glass ceramic powder and basic glass powder;

[0007] Wherein, the chemical composition of the lithium disilicate glass ceramic powder includes, by mass percentage: SiO2, 65-75wt%, Li2O, 13-15wt%, Al2O3, 2-5wt%, K2O, 3-5wt%, P2O5, 2-5%, TiO2, 1-4wt%, F, 0-2wt%;

[0008] In terms of mass percentage, the chemical composition of the basic glass powder includes: SiO2, 40~60wt%, B2O3, 10~20wt%, Li2O, 3~5wt%, Al2O3, 3~10wt%, K2O, 3~10wt%, Na2O, 3~10wt%, F, 2~5wt%, SnO2, 0~2 wt%, CaO, 0~2wt%, and MgO, 0~2wt%.

[0009] Furthermore, the D50 particle size of the lithium disilicate glass ceramic powder is 3 to 50 μm.

[0010] Furthermore, the D50 particle size of the basic glass powder is 3 to 50 μm.

[0011] Furthermore, the D50 particle size of the lithium disilicate glass ceramic powder is 3 to 50 μm; and the D50 particle size of the basic glass powder is 3 to 50 μm.

[0012] Furthermore, when the lithium disilicate microcrystalline dental porcelain powder is used as dentin porcelain, the weight ratio of the lithium disilicate glass ceramic powder to the basic glass powder is: 65-80:35-20.

[0013] Furthermore, when the lithium disilicate microcrystalline dental porcelain powder is used as tooth enamel porcelain, the weight ratio of the lithium disilicate glass ceramic powder to the basic glass powder is: 35-65:65-35.

[0014] Furthermore, when the lithium disilicate microcrystalline dental porcelain powder is used as incisal transparent porcelain, the weight ratio of the lithium disilicate glass ceramic powder to the basic glass powder is 0-15:100-85.

[0015] Based on the same inventive concept, the present invention also provides a method for preparing lithium disilicate microcrystalline dental porcelain powder, to prepare the lithium disilicate microcrystalline dental porcelain powder as mentioned above, comprising the following steps:

[0016] Step S1, preparing lithium disilicate glass ceramic powder;

[0017] Step S2, preparing basic glass powder;

[0018] Step S3, mixing the lithium disilicate glass ceramic powder and the basic glass powder to obtain the lithium disilicate microcrystalline dental ceramic powder.

[0019] Furthermore, the preparation process of the lithium disilicate glass ceramic powder in step S1 is as follows:

[0020] Step S11, quartz sand, lithium carbonate, aluminum hydroxide, potassium carbonate, ammonium dihydrogen phosphate, potassium fluoroaluminate and titanium dioxide are uniformly mixed according to a ratio to obtain a first mixed raw material;

[0021] Step S12, melting the first mixed raw material at high temperature to form a first glass liquid;

[0022] Step S13, pouring the first glass liquid into water for quenching, and drying to obtain first glass slag;

[0023] Step S14, keeping the first glass slag at 530-550° C. for 60-120 min for nucleation treatment, then raising the temperature to 800-850° C. and keeping it for 60-120 min for crystallization treatment, and grinding to obtain the lithium disilicate glass ceramic powder.

[0024] Furthermore, the preparation process of the basic glass powder in step S2 is as follows:

[0025] Step S21, mixing quartz sand, boric acid, lithium carbonate, aluminum hydroxide, potassium carbonate, sodium carbonate, sodium fluorosilicate, tin oxide, calcium carbonate and magnesium oxide in a proportion to obtain a second mixed raw material;

[0026] Step S22, melting the second mixed raw material at high temperature to form a second glass liquid;

[0027] Step S23, pouring the second glass liquid into water for quenching, drying, and ball milling to obtain the basic glass powder.

[0028] The beneficial effects of the present invention are:

[0029] The present invention provides a lithium disilicate microcrystalline dental porcelain powder and a preparation method thereof. The lithium disilicate microcrystalline dental porcelain powder comprises lithium disilicate glass ceramic powder and basic glass powder. The thermal expansion coefficients of the lithium disilicate glass ceramic powder, the basic glass powder and the lithium disilicate microcrystalline dental porcelain powder formed by the above two are all 10 to 11*10 -1 K -1 , which is very compatible with the thermal expansion coefficient of the bottom crown material. At the same time, lithium disilicate glass ceramic powder has high strength, and the rod-shaped crystal interlocking structure it forms can effectively prevent the porcelain layer from cracking; the base glass powder can improve the bonding strength with the bottom crown and prevent the porcelain layer from falling off. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 This is a photograph of the appearance of the lithium disilicate glass ceramic powder prepared in Example 1.

[0032] Figure 2 This is a photograph of the appearance of the basic glass powder prepared in Example 7.

[0033] Figure 3 This is a photograph of the appearance of the lithium disilicate microcrystalline dental porcelain powder used as dentin porcelain prepared in Example 10.

[0034] Figure 4 This is a photograph of the appearance of the lithium disilicate microcrystalline dental porcelain powder used as the incisal transparent porcelain prepared in Example 16.

[0035] Figure 5 This is the SEM test result of the lithium disilicate glass ceramic powder prepared in Example 1.

[0036] Figure 6 This is the XRD test result of the lithium disilicate glass ceramic powder prepared in Example 1.

[0037] Figure 7 This is the comparison effect before and after the denture is sintered in Example 19. DETAILED DESCRIPTION

[0038] The embodiments of the invention are described in detail below with reference to the accompanying drawings.

[0039] Example 1

[0040] A lithium disilicate glass ceramic powder, the specific process is:

[0041] Step S11, 55.37 wt% of quartz sand, 27.38 wt% of lithium carbonate, 4.03 wt% of aluminum hydroxide, 3.92 wt% of potassium carbonate, 5.13 wt% of diammonium phosphate, 1.79 wt% of potassium fluoroaluminate and 2.38 wt% of titanium dioxide are uniformly mixed according to a ratio to obtain a first mixed raw material;

[0042] Step S12, melting the first mixed raw material at a high temperature of 1550° C. to form a first glass liquid;

[0043] Step S13, pouring the first glass liquid into 30° C. cold water for quenching, and drying at 120° C. to obtain first glass slag;

[0044] Step S14, keeping the first glass slag at 530° C. for 120 minutes for nucleation treatment, then raising the temperature to 800° C. for 120 minutes for crystallization treatment, and grinding for 120 minutes to 600 minutes to obtain lithium disilicate glass ceramic powder.

[0045] After testing, the chemical composition of lithium disilicate glass ceramic powder includes: SiO2, 70wt%, Li2O, 14wt%, Al2O3, 4wt%, K2O, 4%, P2O5, 4%, TiO2, 3wt%, F, 1wt%.

[0046] The thermal expansion coefficient of lithium disilicate glass ceramic powder is: 10.3*10 -6 K -1 , D50 particle size: 3~50μm.

[0047] Attached Figure 1 The appearance of the prepared lithium disilicate glass ceramic powder is shown in FIG. 1 , which is in the form of white powder. Figure 5 The SEM test results of lithium disilicate glass ceramic powder are shown in the figure, from which it can be seen that it has a clear rod-shaped crystal structure. Figure 6 FIG. 2 shows the XRD test result of lithium disilicate glass ceramic powder. It can be clearly seen from the figure that lithium disilicate glass ceramic powder has lithium disilicate as the main crystal phase.

[0048] Example 2

[0049] A lithium disilicate glass ceramic powder, the specific process is:

[0050] Step S11, 55.37 wt% of quartz sand, 27.38 wt% of lithium carbonate, 4.03 wt% of aluminum hydroxide, 3.92 wt% of potassium carbonate, 5.13 wt% of diammonium phosphate, 1.79 wt% of potassium fluoroaluminate and 2.38 wt% of titanium dioxide are uniformly mixed according to a ratio to obtain a first mixed raw material;

[0051] Step S12, melting the first mixed raw material at a high temperature of 1550° C. to form a first glass liquid;

[0052] Step S13, pouring the first glass liquid into 30° C. cold water for quenching, and drying at 120° C. to obtain first glass slag;

[0053] Step S14, keeping the first glass slag at 550° C. for 60 minutes for nucleation treatment, then raising the temperature to 850° C. for 60 minutes for crystallization treatment, and grinding for 120 minutes to 600 minutes to obtain lithium disilicate glass ceramic powder.

[0054] After testing, the chemical composition of lithium disilicate glass ceramic powder includes: SiO2, 70wt%, Li2O, 14wt%, Al2O3, 4wt%, K2O, 4%, P2O5, 4% wt%, TiO2, 3wt%, F, 1wt%.

[0055] The thermal expansion coefficient of lithium disilicate glass ceramic powder is: 10.6*10 -6 K -1 , D50 particle size: 3~50μm.

[0056] Example 3

[0057] A lithium disilicate glass ceramic powder, the specific process is:

[0058] Step S11, 55.37 wt% of quartz sand, 27.38 wt% of lithium carbonate, 4.03 wt% of aluminum hydroxide, 3.92 wt% of potassium carbonate, 5.13 wt% of diammonium phosphate, 1.79 wt% of potassium fluoroaluminate and 2.38 wt% of titanium dioxide are uniformly mixed according to a ratio to obtain a first mixed raw material;

[0059] Step S12, melting the first mixed raw material at a high temperature of 1550° C. to form a first glass liquid;

[0060] Step S13, pouring the first glass liquid into 30° C. cold water for quenching, and drying at 120° C. to obtain first glass slag;

[0061] Step S14, keeping the first glass slag at 540° C. for 90 minutes for nucleation treatment, then raising the temperature to 825° C. for 90 minutes for crystallization treatment, and grinding for 120 minutes to 600 minutes to obtain lithium disilicate glass ceramic powder.

[0062] After testing, the chemical composition of lithium disilicate glass ceramic powder includes: SiO2, 70wt%, Li2O, 14wt%, Al2O3, 4wt%, K2O, 4%, P2O5, 4% wt%, TiO2, 3wt%, F, 1wt%.

[0063] The thermal expansion coefficient of lithium disilicate glass ceramic powder is: 10.5*10 -6 K -1 , D50 particle size: 3~50μm.

[0064] Example 4

[0065] A lithium disilicate glass ceramic powder, the specific process is:

[0066] Step S11, 50.19 wt% of quartz sand, 28.64 wt% of lithium carbonate, 5.11 wt% of aluminum hydroxide, 4.96 wt% of potassium carbonate, 6.26 wt% of diammonium phosphate, 1.75 wt% of potassium fluoroaluminate and 3.09 wt% of titanium dioxide are uniformly mixed according to a ratio to obtain a first mixed raw material;

[0067] Step S12, melting the first mixed raw material at a high temperature of 1550° C. to form a first glass liquid;

[0068] Step S13, pouring the first glass liquid into 30° C. cold water for quenching, and drying at 120° C. to obtain first glass slag;

[0069] Step S14, keeping the first glass slag at 540° C. for 90 minutes for nucleation treatment, then raising the temperature to 825° C. for 90 minutes for crystallization treatment, and grinding for 120 minutes to 600 minutes to obtain lithium disilicate glass ceramic powder.

[0070] After testing, the chemical composition of lithium disilicate glass ceramic powder includes: SiO2, 65wt%, Li2O, 15wt%, Al2O3, 5wt%, K2O, 5wt%, P2O5, 5% wt%, TiO2, 4wt%, F, 1wt%.

[0071] The thermal expansion coefficient of lithium disilicate glass ceramic powder is: 10.3*10 -6 K -1 , D50 particle size: 3~50μm.

[0072] Example 5

[0073] A lithium disilicate glass ceramic powder, the specific process is:

[0074] Step S11, 57.56 wt% of quartz sand, 25.70 wt% of lithium carbonate, 5.29 wt% of aluminum hydroxide, 4.55 wt% of potassium carbonate, 3.89 wt% of diammonium phosphate, 1.81 wt% of potassium fluoroaluminate and 1.2 wt% of titanium dioxide are uniformly mixed according to a ratio to obtain a first mixed raw material;

[0075] Step S12, melting the first mixed raw material at a high temperature of 1550° C. to form a first glass liquid;

[0076] Step S13, pouring the first glass liquid into 30° C. cold water for quenching, and drying at 120° C. to obtain first glass slag;

[0077] Step S14, keeping the first glass slag at 540° C. for 90 minutes for nucleation treatment, then raising the temperature to 825° C. for 90 minutes for crystallization treatment, and grinding for 120 minutes to 600 minutes to obtain lithium disilicate glass ceramic powder.

[0078] After testing, the chemical composition of lithium disilicate glass ceramic powder includes: SiO2, 72wt%, Li2O, 13wt%, Al2O3, 5wt%, K2O, 4.5wt%, P2O5, 3wt%, TiO2, 1.5wt%, F, 1wt%.

[0079] The thermal expansion coefficient of lithium disilicate glass ceramic powder is: 10.3*10 -1 K -1 , D50 particle size: 3~50μm.

[0080] Example 6

[0081] A lithium disilicate glass ceramic powder, the specific process is:

[0082] Step S11, 60.15 wt% of quartz sand, 28 wt% of lithium carbonate, 2.12 wt% of aluminum hydroxide, 2.5 wt% of potassium carbonate, 4.61 wt% of diammonium phosphate, 1.82 wt% of potassium fluoroaluminate and 0.8 wt% of titanium dioxide are uniformly mixed according to a ratio to obtain a first mixed raw material;

[0083] Step S12, melting the first mixed raw material at a high temperature of 1550° C. to form a first glass liquid;

[0084] Step S13, pouring the first glass liquid into 30° C. cold water for quenching, and drying at 120° C. to obtain first glass slag;

[0085] Step S14, keeping the first glass slag at 540° C. for 90 minutes for nucleation treatment, then raising the temperature to 825° C. for 90 minutes for crystallization treatment, and grinding for 120 minutes to 600 minutes to obtain lithium disilicate glass ceramic powder.

[0086] After testing, the chemical composition of lithium disilicate glass ceramic powder includes: SiO2, 75wt%, Li2O, 14wt%, Al2O3, 2.21wt%, K2O, 3wt%, P2O5, 3.79wt%, TiO2, 1wt%, and F, 1wt%.

[0087] The thermal expansion coefficient of lithium disilicate glass ceramic powder is: 10.5*10 -1 K -1 , D50 particle size: 3~50μm.

[0088] Example 7

[0089] A basic glass powder, the specific process is:

[0090] Step S21, 39.3 wt% of quartz sand, 27.01 wt% of boric acid, 7.56 wt% of lithium carbonate, 7.6 wt% of aluminum hydroxide, 6.73 wt% of potassium carbonate, 5.66 wt% of sodium carbonate, 4.7 wt% of sodium fluorosilicate, 0.38 wt% of tin oxide, 0.68 wt% of calcium carbonate and 0.38 wt% of magnesium oxide are uniformly mixed according to a ratio to obtain a second mixed raw material;

[0091] Step S22, melting the second mixed raw material at 1400° C. to form a second glass liquid;

[0092] Step S23, pouring the second glass liquid into 30° C. cold water for quenching, drying at 120° C., and ball milling for 120-600 min to obtain basic glass powder.

[0093] After testing, the chemical composition of the basic glass powder includes: SiO2, 53wt%, B2O3, 20wt%, Li2O, 4wt%, Al2O3, 6.5wt%, K2O, 6wt%, Na2O, 6wt%, F, 3wt%, SnO2, 0.5 wt%, CaO, 0.5wt%, and MgO, 0.5wt%.

[0094] The thermal expansion coefficient of the basic glass powder is: 10.1*10 -6 K -1 , D50 particle size: 3~50μm.

[0095] Attached Figure 2 The appearance of the prepared basic glass powder is shown in FIG. , which is in the form of white powder.

[0096] Example 8

[0097] A basic glass powder, the specific process is:

[0098] Step S21, 28.09 wt% of quartz sand, 25.88 wt% of boric acid, 9.05 wt% of lithium carbonate, 7.28 wt% of aluminum hydroxide, 10.74 wt% of potassium carbonate, 9.04 wt% of sodium carbonate, 7.5 wt% of sodium fluorosilicate, 0.36 wt% of tin oxide, 1.33 wt% of calcium carbonate and 0.73 wt% of magnesium oxide are uniformly mixed according to a ratio to obtain a second mixed raw material;

[0099] Step S22, melting the second mixed raw material at 1400° C. to form a second glass liquid;

[0100] Step S23, pouring the second glass liquid into 30° C. cold water for quenching, drying at 120° C., and ball milling for 120-600 min to obtain basic glass powder.

[0101] After testing, the chemical composition of the basic glass powder includes: SiO2, 41wt%, B2O3, 20wt%, Li2O, 5wt%, Al2O3, 6.5wt%, K2O, 10wt%, Na2O, 10wt%, F, 5wt%, SnO2, 0.5wt%, CaO, 1wt%, and MgO, 1wt%.

[0102] The thermal expansion coefficient of the basic glass powder is: 10.8*10 -6 K -1 , D50 particle size: 3~50μm.

[0103] Example 9

[0104] A basic glass powder, the specific process is:

[0105] Step S21, quartz sand 46.18wt%, boric acid 14.23wt%, lithium carbonate 9.95wt%, aluminum hydroxide 8wt%, potassium carbonate 3.54wt%, sodium carbonate 7.21wt%, sodium fluorosilicate 8.25wt%, tin oxide 0.4wt%, calcium carbonate 1.44wt% and magnesium oxide 0.8wt% are mixed uniformly according to a ratio to obtain a second mixed raw material;

[0106] Step S22, melting the second mixed raw material at 1400° C. to form a second glass liquid;

[0107] Step S23, pouring the second glass liquid into 30° C. cold water for quenching, drying at 120° C., and ball milling for 120-600 min to obtain basic glass powder.

[0108] After testing, the chemical composition of the basic glass powder includes: SiO2, 60wt%, B2O3, 10wt%, Li2O, 5wt%, Al2O3, 6.5wt%, K2O, 3wt%, Na2O, 8wt%, F, 5wt%, SnO2, 0.5 wt%, CaO, 1wt%, and MgO, 1wt%.

[0109] The thermal expansion coefficient of the basic glass powder is: 10.6*10 -6 K -1 , D50 particle size: 3~50μm.

[0110] In Examples 1 to 6, the ball milling time is adjusted to obtain lithium disilicate glass ceramic powder with a D50 particle size of 3 to 50 μm. Similarly, in Examples 7 to 9, the ball milling time is adjusted to obtain basic glass powder with a D50 particle size of 3 to 50 μm.

[0111] Since the particle sizes of dentin porcelain, enamel porcelain and incisal transparent porcelain are different, in practice, the corresponding D50 particle size of lithium disilicate glass ceramic powder and basic glass powder will be selected according to the corresponding products for compounding to obtain dentin porcelain, enamel porcelain or incisal transparent porcelain with the corresponding particle size.

[0112] Example 10

[0113] A lithium disilicate microcrystalline dental porcelain powder, used as dentin porcelain, is prepared by mixing the lithium disilicate glass ceramic powder in Example 1 and the basic glass powder in Example 7 in a mass ratio of 65:35.

[0114] After testing, the thermal expansion coefficient of lithium disilicate microcrystalline dental porcelain powder is: 10.23*10 -6 K -1 , D50 particle size: 40μm.

[0115] Lithium disilicate microcrystalline dental porcelain powder was used to prepare porcelain-bonded samples for testing according to ISO 9693-2:2016 standard, and the porcelain-bonding strength of dental ceramics was measured to be 35 MPa.

[0116] Attached Figure 3 The figure shows the appearance of lithium disilicate microcrystalline dental porcelain powder used as dentin porcelain, which is in the form of white powder.

[0117] Embodiment 11

[0118] A lithium disilicate microcrystalline dental porcelain powder, used as dentin porcelain, is prepared by mixing the lithium disilicate glass ceramic powder in Example 2 and the basic glass powder in Example 8 in a mass ratio of 72:28.

[0119] After testing, the thermal expansion coefficient of lithium disilicate microcrystalline dental porcelain powder is: 10.66*10 -6 K -1 , D50 particle size: 40μm.

[0120] Lithium disilicate microcrystalline dental porcelain powder was used to prepare porcelain-bonded samples for testing according to ISO 9693-2:2016 standard, and the porcelain-bonding strength of the dental ceramics was measured to be 38 MPa.

[0121] Example 12

[0122] A lithium disilicate microcrystalline dental porcelain powder, used as dentin porcelain, is prepared by mixing the lithium disilicate glass ceramic powder in Example 3 and the basic glass powder in Example 9 in a mass ratio of 80:20.

[0123] After testing, the thermal expansion coefficient of lithium disilicate microcrystalline dental porcelain powder is: 10.52*10 -6 K -1 , D50 particle size: 40μm.

[0124] Lithium disilicate microcrystalline dental porcelain powder was used to prepare porcelain-bonded samples for testing according to ISO 9693-2:2016 standard, and the porcelain-bonding strength of dental ceramics was measured to be 34 MPa.

[0125] Example 13

[0126] A lithium disilicate microcrystalline dental porcelain powder, used as tooth enamel porcelain, is prepared by mixing the lithium disilicate glass ceramic powder in Example 4 and the basic glass powder in Example 7 in a mass ratio of 35:65.

[0127] After testing, the thermal expansion coefficient of lithium disilicate microcrystalline dental porcelain powder is: 10.17*10 -6 K -1 , D50 particle size: 35μm.

[0128] Lithium disilicate microcrystalline dental porcelain powder was used to prepare porcelain-bonded samples for testing according to ISO 9693-2:2016 standard, and the porcelain-bonding strength of the dental ceramics was measured to be 38 MPa.

[0129] Embodiment 14

[0130] A lithium disilicate microcrystalline dental porcelain powder, used as tooth enamel porcelain, is prepared by mixing the lithium disilicate glass ceramic powder in Example 5 and the basic glass powder in Example 8 in a mass ratio of 50:50.

[0131] After testing, the thermal expansion coefficient of lithium disilicate microcrystalline dental porcelain powder is: 10.55*10 -6 K -1 , D50 particle size: 35μm.

[0132] Lithium disilicate microcrystalline dental porcelain powder was used to prepare porcelain-bonded samples for testing according to ISO 9693-2:2016 standard, and the porcelain-bonding strength of the dental ceramics was measured to be 36 MPa.

[0133] Embodiment 15

[0134] A lithium disilicate microcrystalline dental porcelain powder, used as tooth enamel porcelain, is prepared by mixing the lithium disilicate glass ceramic powder in Example 6 and the basic glass powder in Example 9 in a mass ratio of 65:35.

[0135] After testing, the thermal expansion coefficient of lithium disilicate microcrystalline dental porcelain powder is: 10.43*10 -6 K -1 , D50 particle size: 35μm.

[0136] Lithium disilicate microcrystalline dental porcelain powder was used to prepare porcelain-bonded samples for testing according to ISO 9693-2:2016 standard, and the porcelain-bonding strength of dental ceramics was measured to be 35 MPa.

[0137] Example 16

[0138] A lithium disilicate microcrystalline dental porcelain powder, used as an incisional transparent porcelain, is prepared by mixing the lithium disilicate glass ceramic powder in Example 1 and the basic glass powder in Example 7 in a mass ratio of 15:85.

[0139] After testing, the thermal expansion coefficient of lithium disilicate microcrystalline dental porcelain powder is: 10.13*10 -6 K -1 , D50 particle size: 30μm.

[0140] Lithium disilicate microcrystalline dental porcelain powder was used to prepare porcelain-bonded samples for testing according to ISO 9693-2:2016 standard, and the porcelain-bonding strength of the dental ceramics was measured to be 38 MPa.

[0141] Attached Figure 4 FIG. 3 shows the appearance of lithium disilicate microcrystalline dental porcelain powder used as incisal transparent porcelain, which is in the form of white powder.

[0142] Embodiment 17

[0143] A lithium disilicate microcrystalline dental porcelain powder, used as an incisional transparent porcelain, is prepared by mixing the lithium disilicate glass ceramic powder in Example 1 and the basic glass powder in Example 7 in a mass ratio of 8:92.

[0144] After testing, the thermal expansion coefficient of lithium disilicate microcrystalline dental porcelain powder is: 10.12*10 -6 K -1 , D50 particle size: 20μm.

[0145] Lithium disilicate microcrystalline dental porcelain powder was used to prepare porcelain-bonded samples for testing according to ISO 9693-2:2016 standard, and the porcelain-bonding strength of dental ceramics was measured to be 40 MPa.

[0146] Embodiment 18

[0147] A lithium disilicate microcrystalline dental porcelain powder, used as an incisional transparent porcelain, is prepared by mixing the lithium disilicate glass ceramic powder in Example 1 and the basic glass powder in Example 7 in a mass ratio of 0:100.

[0148] After testing, the thermal expansion coefficient of lithium disilicate microcrystalline dental porcelain powder is: 10.1*10 -6 K -1 , D50 particle size: 6μm.

[0149] Lithium disilicate microcrystalline dental porcelain powder was used to prepare porcelain-bonded samples for testing according to ISO 9693-2:2016 standard, and the porcelain-bonding strength of the dental ceramics was measured to be 42 MPa.

[0150] Embodiment 19

[0151] The dentin porcelain in Example 10, the enamel porcelain in Example 13 and the incisal transparent porcelain in Example 16 were successively molded on the bottom crown from the inside to the outside, and the denture was obtained after sintering. Figure 7 As shown in the figure. The first one from left to right is the effect before sintering, and the other two are the effects after sintering. As can be seen from the figure, the surface of the denture is relatively rough before sintering, while the denture after sintering is slightly yellowish as a whole, and the outer layer is translucent, which is completely comparable to natural teeth.

Claims

1. A lithium disilicate microcrystalline dental porcelain powder, characterized in that: Including lithium disilicate glass ceramic powder and basic glass powder; Wherein, the chemical composition of the lithium disilicate glass ceramic powder includes, by mass percentage: SiO2, 65-75wt%, Li2O, 13-15wt%, Al2O3, 2-5wt%, K2O, 3-5wt%, P2O5, 2-5%, TiO2, 1-4wt%, F, 0-2wt%; In terms of mass percentage, the chemical composition of the basic glass powder includes: SiO2, 40~60wt%, B2O3, 10~20wt%, Li2O, 3~5wt%, Al2O3, 3~10wt%, K2O, 3~10wt%, NaO2, 3~10wt%, F, 2~5wt%, SnO2, 0~2 wt%, CaO, 0~2wt%, and MgO, 0~2wt%.

2. The lithium disilicate microcrystalline dental porcelain powder according to claim 1, characterized in that: The D50 particle size of the lithium disilicate glass ceramic powder is 3 to 50 μm.

3. The lithium disilicate microcrystalline dental porcelain powder according to claim 1, characterized in that: The D50 particle size of the basic glass powder is 3 to 50 μm.

4. The lithium disilicate microcrystalline dental porcelain powder according to claim 1, characterized in that: The D50 particle size of the lithium disilicate glass ceramic powder is 3 to 50 μm; the D50 particle size of the basic glass powder is 3 to 50 μm.

5. The lithium disilicate microcrystalline dental porcelain powder according to any one of claims 1 to 4, wherein when the lithium disilicate microcrystalline dental porcelain powder is used as dentin porcelain, the weight ratio of the lithium disilicate glass ceramic powder to the basic glass powder is 65-80:35-20.

6. The lithium disilicate microcrystalline dental porcelain powder according to any one of claims 1 to 4, wherein when the lithium disilicate microcrystalline dental porcelain powder is used as tooth enamel porcelain, the weight ratio of the lithium disilicate glass ceramic powder to the basic glass powder is 35-65:65-35.

7. The lithium disilicate microcrystalline dental porcelain powder according to any one of claims 1 to 4, wherein when the lithium disilicate microcrystalline dental porcelain powder is used as incisal transparent porcelain, the weight ratio of the lithium disilicate glass ceramic powder to the basic glass powder is 0-15:100-85.

8. A method for preparing lithium disilicate microcrystalline dental porcelain powder, to obtain the lithium disilicate microcrystalline dental porcelain powder as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Step S1, preparing lithium disilicate glass ceramic powder; Step S2, preparing basic glass powder; Step S3, mixing the lithium disilicate glass ceramic powder and the basic glass powder to obtain the lithium disilicate microcrystalline dental ceramic powder.

9. The method for preparing lithium disilicate microcrystalline dental porcelain powder according to claim 8, characterized in that: The preparation process of the lithium disilicate glass ceramic powder in step S1 is as follows: Step S11, quartz sand, lithium carbonate, aluminum hydroxide, potassium carbonate, ammonium dihydrogen phosphate, potassium fluoroaluminate and titanium dioxide are uniformly mixed according to a ratio to obtain a first mixed raw material; Step S12, melting the first mixed raw material at high temperature to form a first glass liquid; Step S13, pouring the first glass liquid into water for quenching, and drying to obtain first glass slag; Step S14, keeping the first glass slag at 530-550° C. for 60-120 min for nucleation treatment, then raising the temperature to 800-850° C. and keeping it for 60-120 min for crystallization treatment, and grinding to obtain the lithium disilicate glass ceramic powder.

10. The method for preparing lithium disilicate microcrystalline dental porcelain powder according to claim 8, characterized in that: The preparation process of the basic glass powder in step S2 is as follows: Step S21, mixing quartz sand, boric acid, lithium carbonate, aluminum hydroxide, potassium carbonate, sodium carbonate, sodium fluorosilicate, tin oxide, calcium carbonate and magnesium oxide in a proportion to obtain a second mixed raw material; Step S22, melting the second mixed raw material at high temperature to form a second glass liquid; Step S23, pouring the second glass liquid into water for quenching, drying, and ball milling to obtain the basic glass powder.

Citation Information

Patent Citations

  • Bonding agent for zirconium oxide and lithium disilicate glass ceramic, and preparation method and application of bonding agent

    CN109279781A

  • Dental ceramic material and molded body of dental ceramic

    JP1993301809A

  • Dental ceramics material and dental ceramics molded article

    JP1994040840A

  • Process for producing a sintered lithium disilicate glass ceramic dental restoration and kit of parts

    US20220125561A1